2011
DOI: 10.1259/bjr/97637841
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic radiation force impulse elastography in distinguishing hepatic haemangiomata from metastases: preliminary observations

Abstract: Objective: The increasing quality of diagnostic ultrasound has resulted in the detection of greater numbers of potentially benign hepatic lesions. Current radiological practice requires contrast enhanced ultrasound, CT or MRI to confirm the diagnosis. Acoustic radiation force impulse (ARFI) elastography is an imaging technique measuring the elasticity of biological tissues. Recent technical advances in ultrasound have made it possible to generate shear waves, whose velocity in the liver is proportional to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 15 publications
7
45
2
Order By: Relevance
“…In opposition, Cho et al, 13 Davies and Koenen, 15 and Shuang-Ming et al 17 showed a significant difference between benign and malignant tumors with cutoff values for discriminating benign from malignant tumors of 2, 2.5, and 2.22 m/s, respectively. However, in the first two studies, 13,15 only hemangiomas were included in the benign tumor group, and in the third study, 17 the benign tumor group (n = 36) was mostly represented by hemangioma (n = 28), with only few focal nodular hyperplasia tumors (n = 7) and 1 adenoma. In addition, we clearly showed that focal nodular hyperplasia and adenoma can be associated with very high ARFI values.…”
Section: Can Arfi Elastography Be Useful In Clinical Practice To Idenmentioning
confidence: 97%
See 2 more Smart Citations
“…In opposition, Cho et al, 13 Davies and Koenen, 15 and Shuang-Ming et al 17 showed a significant difference between benign and malignant tumors with cutoff values for discriminating benign from malignant tumors of 2, 2.5, and 2.22 m/s, respectively. However, in the first two studies, 13,15 only hemangiomas were included in the benign tumor group, and in the third study, 17 the benign tumor group (n = 36) was mostly represented by hemangioma (n = 28), with only few focal nodular hyperplasia tumors (n = 7) and 1 adenoma. In addition, we clearly showed that focal nodular hyperplasia and adenoma can be associated with very high ARFI values.…”
Section: Can Arfi Elastography Be Useful In Clinical Practice To Idenmentioning
confidence: 97%
“…[13][14][15][16][17] Kato et al 31 were among the first to determine qualitative cartography of the elasticity of different liver tumors by real-time elastography. They showed that hemangioma was a soft tumor, metastases were hard tumors, and hepatocellular carcinoma was in between.…”
Section: Can Arfi Elastography Be Useful In Clinical Practice To Idenmentioning
confidence: 99%
See 1 more Smart Citation
“…The unit of ARFI is m/sec. Operator independency and the quantitative data presentation are the advantages of ARFI, but does not have capability to present data in ascites mediums like in SWE 22,[26][27][28] . TE is one of the methods that use shear-waves.…”
Section: (Acoustic Radiation Force Impulse Elastography Shear-wave Ementioning
confidence: 99%
“…Additionally, the characterization and/or differentiation of pathological tissues by US elastography have increasingly been evaluated by numerous up-to-date studies that aimed to reveal the diagnostic efficacy of US elastography in differentiating benign or malignant conditions. Although the visceral organs, such as the liver [8], kidney [9], spleen [10], pancreas [11], uterus [12], and prostate [13], were the main subjects in these studies, the utility of US in assessing pathologies of the thyroid glands [14][15][16] and breast tissue [17][18][19] have also been evaluated by a substantial number of researchers. In comparison, only a limited number of studies in the literature have reported the validity of using US elastography in clinical practice for patients with musculoskeletal issues.…”
Section: Introductionmentioning
confidence: 99%